Dynamic Changes in the Quantitative Electroencephalographic Spectrum During Attention Tasks in Patients With Prader–Willi Syndrome - Tsai, Li-Ping; Wang, Syu-Siang; Chee, Siew-Yin; Wong, Shi-Bing (Frontiers in Genetics, 2022)
Introduction: Attention problems are frequently observed in patients with Prader–Willi syndrome (PWS); however, only few studies have investigated the severity and mechanisms of attention problems in them. In this study, we aim to evaluate dynamic changes in the quantitative electroencephalographic (EEG) spectrum during attention tasks in patients with Prader–Willi syndrome (PWS). Method: From January to June 2019, 10 patients with PWS and 10 age-matched neurotypical control participants were recruited at Taipei Tzu Chi Hospital. Each participant completed Conners’ continuous performance test 3rd edition (CPT-3) tasks with simultaneous EEG monitoring. The dynamic changes in the quantitative EEG spectrum between the resting state and during CPT-3 tasks were compared. Results: Behaviorally, patients with PWS experienced significant attention problems, indicated by the high scores for several CPT-3 variables. The theta/beta ratio of the resting-state EEG spectrum revealed no significant differences between control participants and patients with PWS. During CPT-3 tasks, a significant decrease in alpha power was noted in controls compared with that in patients with PWS. The attention-to-resting alpha power ratio was positively correlated with many CPT-3 variables. After adjusting for genotype, age, intelligence, and body mass index, the attention-to-resting alpha power ratio was still significantly correlated with participants’ commission errors. Conclusion: This study provides evidence that attention problems are frequently observed in patients with PWS, while attention impairment can be demonstrated by dynamic changes in the quantitative EEG spectrum.